More frequent burning increases vulnerability of Alaskan boreal black spruce forests. (23rd August 2016) - Hoy, Elizabeth E; Turetsky, Merritt R; Kasischke, Eric S
Abstract: Much recent research has investigated the effects of burning on mature black spruce ( Picea mariana ) forests in interior Alaska, however little research has focused on how frequent reburning affects soil organic layer (SOL) vulnerability in these ecosystems. We compared organic soil layer characteristics in black spruce stands that burned after two fire-free intervals (FFI), including an intermediate-interval (37–52 years) and a more typical long-interval (70–120 years). We found that depth of burn varied significantly between intermediate-interval and long-interval sites, and as there was less material available to burn in intermediate-interval stands, percent depth reduction was greater in these stands (78.9% ± 2.6%) than in long-interval stands (62.9% ± 1.5%). As a result, less residual organic soil carbon remained post-fire in intermediate-interval than long-interval stands. Post-fire organic soil carbon stocks averaged 0.51 ± 0.08 kg C m −2 in the intermediate-interval sites, which is less than estimates of soil carbon stock for long-interval fire events (ranging from 2.07 to 5.74 kg C m −2 ). In addition to altering soil carbon storage, a depletion of the SOL during more frequent fire events will likely delay the recovery of permafrost and could trigger a change in the possible successional trajectory of a site, from black spruce dominated to deciduous or even shrub dominated ecosystems in the future.